DARI PENGUNGSIAN KE KEJAYAAN: DISKURSUS DINASTI UMAYYAH II DAN DAMPAK TRANSFORMASINYA DI ANDALUSIA PADA ABAD PERTENGAHAN - Moona Maghfirah; Raden Muhammad Syahrial (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
This article examines the journey of the Umayyad Dynasty II from exile in the Middle East to achieving glory in Andalusia, as well as the transformational impact they had on the region. The Umayyad II dynasty, led by Abd al-Rahman I, succeeded in turning Andalusia into an advanced center of political, economic and cultural power in medieval Europe. Through theoretical and historical analysis, this article explores the factors that supported the progress of Andalusia under the leadership of Umayyah II, using historical methods consisting of heuristics, criticism, interpretation and historiography. The results of this study can be seen, including visionary leadership, religious tolerance, cross-cultural cooperation, infrastructure development, scientific development, and investment in arts and education. The Umayyad II Dynasty's contribution to Andalusia included political, social and cultural transformation. They succeeded in creating an inclusive environment where Muslims, Christians and Jews could live side by side peacefully, and enriched the intellectual and cultural life of the region. This discourse also provides theoretical insight into political adaptation, social inclusiveness, and cultural investment in creating significant changes in the history of discourse of the Umayyad Dynasty II in Andalusia.